Application of cereal-bran sourdoughs to enhance technological functionality of white wheat bread supplemented with pumpkin (Cucurbita pepo) puree. (15th March 2022) - Ebrahimi, Maryam; Ali Noori, Seyyed Mohammad; Sadeghi, Alireza; Coban, Ozlem emir; Zanganeh, Javad; Ghodsmofidi, Seyed Mofid; Malvandi, Zahra; Raeisi, Mojtaba
Abstract: Bread enrichment with fruits, vegetables and cereal brans as nutraceutical carriers is very crucial in the developing countries. In the present study, screening-based acidification activity was used to select lactic acid bacteria (LAB) isolated from the wheat bran sourdough (WBS). Then the screened LAB was identified and used as a sourdough starter culture. Subsequently, response surface methodology (RSM) was used to investigate the combined effects of pumpkin puree and different cereal bran sourdoughs including WBS, barley bran sourdough (BBS), and rice bran sourdough (RBS) fermented with the selected LAB isolate on quality characteristics of the white loaf bread. The results revealed that pumpkin puree and cereal-bran sourdoughs synergistically improved the textural and sensorial properties of the product. The formulation containing 20% pumpkin puree, 10% BBS, 7.67% RBS and 7% WBS was found as the optimum formulation for white loaf bread. In the optimum formulation the hardness, porosity, total color difference, phytic acid content, and overall acceptability were measured at 2.08 N, 36.55%, 14.70, 180.50 (mg/100 g), and 3.81, respectively. Accordingly, the technological functionalities of the fortified bread were remarkably improved compare to the control sample. Highlights: Lactic acid bacteria were isolated from wheat bran sourdough. LAB were used to produce wheat bread with pumpkin puree and RBS, BBS, and WBS. Textural and sensorial properties of bread were improved. Sourdough prepared using barley bran was exhibited the best results. A remarkable decreased in phytic acid content of the pan loaf bread was observed.